Risk factor for premature rupture of membranes: a clinical study - Purnamawati, Intan (International Journal of Research in Medical Sciences, 2024)
Background: Premature rupture of membranes (PROM) is the rupture of the amniotic membrane before the onset of labour. Based on the time of occurrence, PROM can be divided into two, namely Premature Rupture of Membranes (PROM) and Preterm Premature Rupture of Membranes (PPROM). PROM occurs at or after 37 weeks gestation. PPROM, occurs before 37 weeks gestation. Methods: This study is a descriptive retrospective analytical observational study with cross sectional method. This research uses SPSS data processing. Data were taken from the medical records of inpatients in the maternity ward at Bima Hospital in the period January-December 2023. Results: The results of the analysis showed that there was a significant relationship in the maternal age factor of less than 20 years by 70.6%. Risk factors in the education sample were most prevalent in low education level at 62.7%. The risk factor of gestational age of the sample was mostly found in preterm gestation (less than 37 weeks) showing a significant relationship to the incidence of PROM by 66.6%. In the risk factor of parity most in primigravida is 66.6%. Conclusions: In this study there is a relationship of risk factors that affect the occurrence of premature rupture of membranes in the maternity ward of Bima Hospital, namely maternal age less than 20 years, low education level, with preterm gestational age or less than 37 weeks and primigravida parity.